2005
DOI: 10.1080/00049530500141022
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Reciprocity: The effect of reciprocity, carer self-esteem and motivation on the experience of caregiver burden

Abstract: Caregiver burden can be alleviated by a sense of reciprocity or balance in the give-and-take between a caregiver and carereceiver (Dwyer & Miller, 1990). This study investigated whether self-esteem and intrinsic motivation influence the relationship between reciprocity and caregiver burden. Primary caregivers (N = 56) of a patient with a disability, illness or frailty due to aging were recruited via carer organisations. Participants completed the Caregiver Burden Inventory (Novak & Guest, 1989a), the Caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 45 publications
7
47
0
1
Order By: Relevance
“…Additional challenges that may accompany caregiving include feeling strain and stresses, experiencing increased time commitment and a dwindling social life, getting too involved, getting too attached, and feelings of guilt when the CR needs more care than the friend can provide (Barker, 2002; Nocon & Pearson, 2000). Research on caregiving and reciprocity found that some of the negative effects of caregiving to be decreased by reciprocal warmth between the CG and recipient of care (Reid, Moss, & Hyman, 2005). …”
Section: Non-kin Caregivingmentioning
confidence: 99%
“…Additional challenges that may accompany caregiving include feeling strain and stresses, experiencing increased time commitment and a dwindling social life, getting too involved, getting too attached, and feelings of guilt when the CR needs more care than the friend can provide (Barker, 2002; Nocon & Pearson, 2000). Research on caregiving and reciprocity found that some of the negative effects of caregiving to be decreased by reciprocal warmth between the CG and recipient of care (Reid, Moss, & Hyman, 2005). …”
Section: Non-kin Caregivingmentioning
confidence: 99%
“…Caregiver burden has been noted to decrease with a sense of reciprocity or balance of exchange within the caregiving dyad (Reid, Moss, & Hyman, 2005;author, 1996;Donorfio & Sheehan, 2001). Some filial caregivers in their "expression of friendship and love" may seem to go "beyond the call of duty."…”
Section: Filial Caregiving: Expression Of Friendship and Lovementioning
confidence: 99%
“…The transition to a caregiving relationship is frequently marked by a loss of reciprocity between relationship partners, making acts of helping feel more burdensome for the caregiver (e.g., Neufeld & Harrison, 1995; Pearlin, Mullan, Semple, & Skaff, 1990; Reid, Moss, & Hyman, 2005). In the absence of reciprocity, other aspects of the relationship between caregiver and care recipient may influence the effects of helping.…”
mentioning
confidence: 99%
“…In most prior work, caregiving has been defined without reference to caregiver behavior—for example, as witnessing a loved one’s illness (Cacioppo et al, 1998) or hospitalization of the spouse (Christakis & Allison, 2006). This limitation has been present specifically in research on the relationship between caregiver and care recipient as a moderator of wellbeing outcomes (e.g., Reid et al, 2005; Uchino, Kiecolt-Glaser, & Cacioppo, 1994; Williamson & Schulz, 1990; Williamson et al, 1998). Moreover, research that has specifically assessed time spent caregiving—as distinct from being a caregiver— has typically not distinguished between (possibly beneficial) active helping and time spent on call (e.g., Amirkhanyan & Wolf, 2003; Arai & Ueda, 2003; S.…”
mentioning
confidence: 99%